ENHANCEMENT OF FISH YIELD BY ENRICHMENT OF PLANKTON THROUGH ORGANIC MANURE - BARUA, DEEPJYOTI; GHOSH, TAPAS KUMAR; BERA, PUJADEBI (Journal of the Inland Fisheries Society of India, 2026)
The experiment was undertaken to study both the qualitative and quantitative enrichment of phytoplankton and zooplankton using different organic manures and their impact on the growth of Cirrhinus mrigala. Cisterns (180 L) were treated with three types of organic manures, namely cow dung (T2), pig dung (T3), and poultry manure (T4), along with a control (T1). Manures were applied on an isonitrogen basis, considering 10,000 kg cow dung/ha as the initial dose. Periodical manuring was applied at half of the initial dose at monthly intervals. The total volume and protein content of plankton were found to be higher with poultry manure. Fish yield was highest in poultry manure (4963.2 kg/ ha/90 days) compared to pig dung (3667.2 kg/ha/90 days) and cow dung (2440.8 kg/ha/90 days). The study demonstrates that carp production can be significantly enhanced using organic manure by increasing the availability of enriched plankton to fish.